The Relationship of International Human Rights Law with International Humanitarian Law in Situations of International Armed Conflicts - Lubis, Muhammad Ikhsan (Universitas Negeri Semarang, 2016)
The existence between International Humanitarian Law and Human Rights Law has a different feel from each other, though equally universal. As an example of mistreatment of prisoners of war committed by US Occupation Forces in Iraq, surely all countries say it is an international crimes (war crimes). This paper would discuss concerning how the relationship the International Human Rights with International Humanitarian Law in Situations of International Armed Conflicts. The paper argued that the relationship between human rights and humanitarian law can be distinguished but not separated. The principles of the UDHR can apply to the International Humanitarian Law, but some of the principles of the UDHR and limited humanitarian law apply in times of peace and times of armed conflict alone. Argued that the gap between International Humanitarian Law by the Human Rights bridged together through the enactment of the principles of human rights and humanitarian law principles that cannot be postponed.